2013
DOI: 10.1016/j.ijcard.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes is not an independent risk factor for incident heart failure, other cardiovascular events or mortality in older adults: Findings from a population-based cohort study

Abstract: Background Whether prediabetes is an independent risk factor for incident heart failure (HF) in non-diabetic older adults remains unclear. Methods Of the 4602 Cardiovascular Health Study participants, age ≥ 65 years, without baseline HF and diabetes, 2157 had prediabetes, defined as fasting plasma glucose (FPG) 100–125 mg/dL. Propensity scores for prediabetes, estimated for each of the 4602 participants, were used to assemble a cohort of 1421 pairs of individuals with and without prediabetes, balanced on 44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Using ADA criteria for IFG, the meta-analysis reported that IFG was not associated with an increased risk of all-cause mortality, compared to normoglycaemia (RR 1.07 95% CI 0.92–1.26), similar to our results. Other additional studies did not find any association between IFG and mortality risk [1921]. Among US participants aged 52–75 years followed for 6.3 years, there was no association between IFG (ADA criteria) and all-cause mortality (HR 0.93; 95% CI 0.70–1.24) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Using ADA criteria for IFG, the meta-analysis reported that IFG was not associated with an increased risk of all-cause mortality, compared to normoglycaemia (RR 1.07 95% CI 0.92–1.26), similar to our results. Other additional studies did not find any association between IFG and mortality risk [1921]. Among US participants aged 52–75 years followed for 6.3 years, there was no association between IFG (ADA criteria) and all-cause mortality (HR 0.93; 95% CI 0.70–1.24) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Various epidemiologic data have shown that prediabetes is associated with a high risk of heart failure and suggest an ageadjusted hazard ratio (HR) between 1.2 and 1.7 in different populations of patients with impaired fasting glucose, 5,6 although not confirmed in all studies. 7 A large communitybased cohort study of 6814 subjects without coronary vascular disease at baseline was followed for 4 years, and the incidence of heart failure, depending on the presence of metabolic syndrome, was analyzed. 8 This study showed that features of metabolic syndrome are associated with an increased risk of heart failure, with two-thirds of patients developing HFrEF.…”
Section: Incidence and Prevalence Of Heart Failure In Diabetesmentioning
confidence: 99%
“…The present results are in line with those of the Deedwania et al . study, in which prediabetes did not provide any risk for the population aged ≥65 years; however, in the Cardiovascular Health Study, a cohort of 4014 individuals aged ≥65 years, impaired glucose tolerance was a significant predictor of CHD and total mortality . However, it should be noted that their analysis was not adjusted for traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the well‐known risks of high blood sugar, recent studies have shown that older people with diabetes who have lower blood sugar levels are at higher risk of all‐cause mortality . Furthermore, a recent study claimed that unlike younger adults, prediabetes was not an independent risk of CVD in older adults who might be exposed to multiple other competing risk factors . These findings, in addition to the growing population with diabetes and prediabetes, and a recent report of the American Diabetes Association and American Geriatric Society about critical knowledge gaps of diabetes among older adults, suggest the urgency of an investigation of different risks of glucose tolerance categories for developing CVD as well as mortality in this particular age group.…”
Section: Introductionmentioning
confidence: 99%